Fungal Keratitis: A Six-Year Review at a Tertiary Referral Centre - Iselin, K. C.; Baenninger, P. B.; Schmittinger-Zirm, A.; Thiel, M. A.; Kaufmann, C. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background This review reports the epidemiology, laboratory results, treatment regimens and costs of fungal keratitis at a tertiary referral center in Lucerne, Switzerland. Patients and Methods Culture-proven fungal infections between January 2010 and December 2015 were reviewed retrospectively. Results Seventeen patients with a mean age of 52 years were identified. Contact lens wear was the most important risk factor (n = 11) (65 % of all cases), with filamentous fungi being identified as the most common fungus type (n = 10) (91 % of all cases of contact lens-associated fungal keratitis). All non-contact lens-associated fungal infections (n = 6) (35 % of all cases) were related to Candida spp. Six patients (35 %) were treated on an outpatient basis; 11 cases (65 %) required hospitalisation. Systemic voriconazole was the treatment regimen prescribed most often (n = 12) (71 %), followed by topical natamycin 5 % (n = 11) (65 %). Corneal crosslinking and penetrating keratoplasty were required in 4 cases each (24 %). One case ended up in enucleation (6 %). Average costs per case were EUR 15 952 for hospitalised patients if surgical intervention was required, and EUR 7415 if no intervention was performed. Average costs for outpatients were EUR 7079. In a majority of cases, visual acuity could be improved (n = 9) (53 %) or preserved (n = 2) (12 %). Conclusion Despite the relatively low incidence of culture-proven keratitis (17 cases in 6 years), a clear pattern with regard to risk factors and fungus species was noted. In the absence of a gold standard for the treatment of fungal keratitis, the combination of systemic voriconazole and topical natamycin seems to be one of the most commonly used antifungal treatment regimens. The costs of outpatient versus inpatient non-surgical treatment were approximately the same.
Keywords: fungal keratitis; contact lenses; antifungal therapy; treatment cost